Learning Environment and Approaches to Learning in China and Australia: A Tale of Three Accounting Cohorts - Riccardo Natoli; Tracey McDowall; Zi Wei; Beverley Jackling (Australasian Accounting, Business and Finance Journal, 2022)
The main purpose of this paper is to investigate whether learning approaches are impacted by the learning environment across two countries and three accounting student cohorts. This paper utilises a logistic regression based on responses from 1,381 students across five higher education (HE) institutions from China and Australia. The findings provide original empirical evidence of the Chinese accounting students’ expectations of deep learning and show that student perceptions of good teaching is a key determinant to a deep approach to learning for all three student cohorts. In addition, clear goals and standards were significant for Chinese accounting students studying both in China and Australia, while appropriate workload was significant for deep learning for the Australian domestic student cohort. There are practical implications for instructors as the results show that instructors need to adjust their teaching accordingly along with adjusting expectations regarding student workload and assessments.
Keywords: Course experience; Learning environment; Approaches to learning; Accounting education; China; Australia